Association of Family Socioeconomic Status and Infectious Diseases with Underweight Among Children Aged 24–59 Months - Nur Mut'mainah; Hairunnisah Hairunnisah; M.Noris M.Noris; Darmin Darmin (Universitas Muhammadiyah Palembang, 2026)
Underweight remains a public health nutrition problem, particularly among children under five years old, because it may affect physical growth, cognitive development, and increase the risk of morbidity. Family socioeconomic status and infectious diseases are considered factors associated with underweight. This study aimed to analyze the relationship between family socioeconomic status and infectious diseases with the incidence of underweight among children aged 24–59 months in the working area of Rasanae Timur Public Health Center, Dodu Village, Bima City. This study employed a quantitative method with a cross-sectional design. The sample consisted of 50 children under five, including 25 cases and 25 controls selected using purposive sampling. Data were collected through interviews using questionnaires, weight measurements, and documentation. Data analysis was conducted using the Chi-Square test with a significance level of p<0.05. The results showed that there was no significant relationship between father’s education level (p=0.553), father’s occupation (p=0.221), mother’s occupation (p=0.514), family income (p=0.480), and infectious diseases (p=0.564) with underweight incidence among children under five. However, a significant relationship was found between mother’s education level and underweight incidence (p=0.010). This study concludes that maternal education plays an important role in fulfilling nutritional needs and child care practices. Therefore, improving maternal knowledge through nutrition education and regular growth monitoring is recommended to prevent underweight among children under five.